Aspects of Achieving Efficiency in the Educational Process on the Basis of an Innovative Approach (Eurasian Journal of Learning and Academic Teaching, 2022)
Before proceeding to the study of the issue of the content and directions of news input in the educational system, let us define the concept of "pedagogical system" and "news input in the pedagogical system". We know that the pedagogical process is established on the basis of the pedagogical system.